Evaluation of Raw and Detoxified Neem Cake in the Diets of Wistar Rats (Rattus norvegicus) as Partial Protein Supplement - Nageswara Rao, S. B. (Indian Journal of Animal Nutrition, 2018)
Present experiments were conducted to test raw and detoxified neem cake as a replacement of soybean meal in the diets of Wistar rats, Replacement of up to 25 % soybean meal with DNC only resulted in positive growth rate (0.60 g/d) in rats compared to control (1.55 g/d). Low levels of DNC supplementation (12.5 % in experiment 1 and 25 % in experiment 2 caused similar nutrient intake and digestibility over control.Â DNC supplementation did not exert any abnormal changes in blood profiles except in elevated AST levels in 37.5% replaced group. Serum testosterone levels were found to be reducing in rats that received DNC at 50% and RNC at 25%. Mild changes in intestinal villi were observed up on histopathological examination in DNC 25 % group. Â Feeding of DNC is definitely better than RNC and replacement of SBM nitrogen with DNC up to 25 % only did not exert adverse changes to cause growth depression, decreased feed consumption, blood profiles and histopathology. Thus, DNC has to be fed with caution at low levels Â for monogastric animals.